Biopolitical precarity in the permeable body: the social lives of people, viruses and their medicines. Issue 3 (27th May 2017) - Mills, Elizabeth
Abstract: This article is based on multi-sited ethnography that traced a dynamic network of actors (activists, policy-makers, health care systems, pharmaceutical companies) and actants (viruses and medicines) that shaped South African women's access to, and embodiment of, antiretroviral therapies (ARVs). Using actor network theory and post-humanist performativity as conceptual tools, the article explores how bodies become the meeting place for HIV and ARVs, or non-human actants. The findings centre around two linked sets of narratives that draw the focus out from the body to situate the body in relation to South Africa's shifting biopolitical landscape. The first set of narratives articulate how people perceive the intra-action of HIV and ARVs in their sustained vitality. The second set of narratives articulate the complex embodiment of these actants as a form biopolitical precarity. These narratives flow into each other and do not represent a totalising view of the effects of HIV and ARVs in the lives of the people with whom I worked. The positive effects of ARVs (as unequivocally essential for sustaining life) were implicit and the precarious vitality of the people in this ethnography was fundamental. However, a related and emergent set of struggles become salient during the study that complicate a view of ARVs as a 'technofix'. These emergent struggles were biopolitical, and they related first to the intra-action of HIV and ARVs 'within' the body; and second, to the 'outside' socio-economic context in which people's bodies were situated.